Evaluation of male factor in assisted reproduction: new technologies - Huamán Guerrero, Moisés (2015)
Objectives: To determine whether volumetric ultrasonography (3D, static and dynamic) provides better information than conventional ultrasound (2D) in the assessment of pregnancy before 7 weeks of amenorrhea. Design: Clinical series of cases study. Setting: Instituto Latinoamericano de Salud Reproductiva – ILSAR. Participants: Pregnant women within the fifth and seventh weeks of pregnancy. Interventions: An endovaginal ultrasound was performed to 30 pregnant women between the fifth and seventh weeks of amenorrhea with a GE Volusson Expert 730 using multifrequency endocavitary transductor (3.7-9.3 MHZ), 75% maximum potency in function ‘Early Pregnancy’ without harmonics; test duration was 5-15 minutes. Once the chorionic sac was localized its content was assessed for the yolk sac and the embryo, first using 2D and then static 3D and dynamic 3D (4D). Main outcome measures: Identification of the yolk sac and the embryo. Results: The yolk sac could be identified using 3D ultrasound in 7 pregnant women with less than 5 weeks and 3 days of gestation, preceding its obsevation with 2D ultrasound  by 3 to 4 days average. Assessment of the embryo before 6 weeks of gestation could be done in 12 pregnancies using 3D ultrasound. Multiplanar technic enhanced sensitivity to detect the embryo earlier. Assessment of the yolk sac, omphalomesenteric duct and embryo in gestations between 6 and 7 weeks was better accomplished with 3D. Conclusions: The use of volumetric ultrasonography (3D/4D) in early pregnancy allowed the identification of the yolk sac and embryo 3 to 4 days before 2D ultrasonography, representing an improvement in interpreting visible structures by obstetricians and parents.